Establishment of the Deep Mine Microbial Observatory (DeMMO), South Dakota, USA, a Geochemically Stable Portal Into the Deep Subsurface - Osburn, Magdalena R.; Kruger, Brittany; Masterson, Andrew L.; Casar, Caitlin P.; Amend, Jan P. (Frontiers in Earth Science, 2019)
Identifying temporal trends in deep subsurface geomicrobiology is challenging as it requires both in-depth knowledge of in situ geochemistry and innovative sampling techniques. Subsurface microbial dynamics can only be understood in the context of accompanying geochemistry, and thus, it is imperative to first characterize available microbial habitats and their temporal evolution. Also, samples must be acquired in a clean and consistent manner to avoid artefacts stemming from surface microbes, atmospheric contamination, or external temporal variability. To facilitate these ends, we established the Deep Mine Microbial Observatory (DeMMO) in the Sanford Underground Research Facility (SURF), Lead, SD, USA to sample naturally draining fracture fluids at six spatially distributed sites from the shallowest (800 ft) to the deepest accessible (4,850 ft) depths. Here we report on the installation and subsequent two-year aqueous geochemical monitoring campaign of the DeMMO network. DeMMO fluids have distinct geochemical compositions showing differences with respect to depth, proximity to mine workings, and host rock geology. Most measurements were remarkably stable through the two-year sampling window, illustrating temporal stability of the water sources to each site, including over induced perturbations such as drilling. Interestingly, there was a lack of seasonality even at shallowest sites, indicating limited direct communication with modern meteoric waters. Patterns of fluid geochemistry are distinct between sites, and largely predictable based upon our understanding of the lithology and inorganic geochemistry of the host rocks. Thermodynamic calculations suggest that both inorganic and organic redox reactions can yield energy to, respectively, lithotrophic and heterotrophic microorganisms in this system, although the yields vary considerably by site. We conclude that each DeMMO site represents a unique window into the deep subsurface of SURF, accessing distinct fluid pockets, aqueous geochemistry, and dissolved gas geochemistry – providing stable conditions that facilitate long-term habitation of subsurface fractures and water pockets by distinct microbial communities.